Exploring the interconnection between sustainability, gentrification mitiga-tion, and marketing theories in johannesburg’s social housing landscape - Makalima, Mzuchumile (Acta Carolus Robertus, 2024)
Urban transformation, especially in the context of social housing, demands a comprehensive and sustainable approach that addresses the interconnected challenges of funding, gentrification, and triple bottom line considerations. This study explores three marketing theories which are Stakeholder Theory, Relationship Marketing, and Green Marketing as integrated frameworks for navigating these complexities. Stakeholder Theory emphasizes inclusive decision-making and ongoing engagement with diverse stakeholders, ensuring the alignment of urban development with community needs. Relationship Marketing brings a customer-centric perspective, fostering trust and collaboration for enduring relationships between urban planners and the community. Green Marketing introduces economic, environmental, and social responsibility, promoting sustainable practices within the triple bottom line framework. Synthesizing these theories provides a holistic strategy for Johannesburg’s social housing paradigm, aiming for gentrification mitigation, and a balance between economic, social, and environmental sustainability. The proposed approach serves as a blueprint for equitable and sustainable urban development globally.